PENYUSUNAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM PADA UMKM BERPOTENSIAL DI KABUPATEN BINTAN KEPULAUAN RIAU - Suci Wahyuliza; Ronia Tambunan (Jurnal Ilmiah Akuntansi dan Finansial Indonesia, 2024)
This study aims to see what factors influence the application of SAK EMKM in preparing financial statements for MSMEs in Bintan Regency. This research data was obtained from a questionnaire with respondents of potential MSME entrepreneurs according to the Department of Cooperatives, Micro Enterprises, Industry and Trade of Bintan Regency. The reason for choosing potential MSMEs is that researchers assume that potential MSMEs are MSMEs that have financial statements. The data collection technique was carried out by collecting questionnaire data from as many as 114 respondents and analyzed using SPSS. Of the 114 respondents who fit the sample criteria, there were 97 respondents, but only 93 respondents filled in the questionnaire. After testing the data, it can be concluded that the variables of accounting understanding, the level of readiness of MSME actors, and the socialization of SAK EMKM affect the preparation of financial statements based on SAK EMKM.